The Preschool Child in Suka_ Village, North Sumatra III. Upper arm Circumference and Skinfolds as Indicators of Nutritional Status - Jane A. Kusin; H. S. R. Parlindungan Sinaga; J. Khoman; J. M. Houtkooper; U. Renqvist (Paediatrica Indonesiana, 1982)
Upper arm circumfereru:e, triceps and subscapular skinfolds were measured at 6-monthly intervals during one year in a group of preschool children, age 0 - 5 years.All 3 measurements decreased as compared with the reference in the age period 1 - 23 months followed by a catch-up at age 2- 4 years.The predictive value of upper arm circumference for the development af malnutrition was low. Age group 1 - 23 months should be considered "at risk" irrespectively of the nutritional state at the time of examination.Absence of mortality may be attributed to the fact that children can eat to appetite, when they are healthy and to the simple medical treatment given.